A bibliometric analysis of nucleic acid probe and its applications in oncology: towards more precise molecular medicine - Xingyu Zhong; Haodong He; Yifan Xiong; Jianxuan Sun; Na Zeng; Shaogang Wang; Qidong Xia (Discover Oncology)
Abstract Background Nucleic acid probes, which are short sequences of nucleic acids designed to complement specific DNA or RNA targets, have broad applications in biosensing, genetic studies, and various other fields. In tumor diagnosis and treatment, nucleic acid probes offer a precise and accessible approach that is essential for improving patient care and quality of life. Despite substantial research on nucleic acid probes over the past three decades, few comprehensive reviews have retrospectively examined the field. Methods This study extracted 30 years of nucleic acid probe-related research articles from the Web of Science Core Collection database. We used CiteSpace, VOSviewer, and R tools to systematically analyze the field’s current status and developmental trends, with an emphasis on applications in oncology. Results Our findings indicate a continuous growth trend in nucleic acid probe research, with the United States and China, along with their leading institutions and authors, making the most significant contributions. In oncology specifically, nucleic acid probe research has focused primarily on signal amplification, liquid biopsy, and drug delivery. The emergence of novel biomarkers and assay techniques has been a pivotal factor driving advancements in this field. Conclusion Nucleic acid probes show strong potential for applications in tumor precise diagnosis and treatment. Continued innovation and closer interdisciplinary collaboration will be vital for further advancements, while large-scale clinical studies are needed to validate their clinical utility.